If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (x + 1) = 156 Reorder the terms: x + (1 + x) = 156 Remove parenthesis around (1 + x) x + 1 + x = 156 Reorder the terms: 1 + x + x = 156 Combine like terms: x + x = 2x 1 + 2x = 156 Solving 1 + 2x = 156 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2x = 156 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 156 + -1 2x = 156 + -1 Combine like terms: 156 + -1 = 155 2x = 155 Divide each side by '2'. x = 77.5 Simplifying x = 77.5
| -7x+7x=+1 | | 6n+6=72 | | 8+x/6=-10 | | 3(y-3)=-2y+6 | | -2x+1=-19+2x | | a^2=9a+36 | | 9/r=3/5 | | 8y-25=2(4y+3) | | 3/8=w/4 | | 27x-9=15 | | 10x-3=7x | | 5x-59=2x-5 | | -16t+116t+101=0 | | 4+3x=x+28 | | 142-3x=33x+22 | | 4(4x+6)=3(2x+18) | | 4+5n=9 | | (w+1)(w+4)= | | 3x/2-4=5 | | 3/4(8a+20)=6a+10 | | -16-6x=8+10x | | 5=23/w | | -16-6x= | | 11x^2-600x-2890=0 | | 2x+3y=400 | | X-42=x | | -5.204-z=-18.148 | | -2,5:12/3-1,4= | | 6x-20=-4x | | 7x-6x+5x-9x= | | (2x-3)+(2x-3)+x+x=60 | | 2x-1=4x+4 |